Thermal Properties of Acetylated Betung Bamboo (Dendrocalamus asper) Pulp – Polypropylene Biocomposites - Wida Banar Kusumaningrum; Sukma Surya Kusumah; Ismadi Ismadi; Rochmadi Rochmadi; Subyakto Subyakto (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2023)
Thermal properties are important factors to determine the proper manufacturing, processing, and storing of biocomposites. Therefore, the thermal properties of the biocomposite made from acetylated betung bamboo pulp and polypropylene (PP) were investigated. The biocomposite was manufactured by hot pressing at 180 oC for 2 minutes and the fiber contents of the acetylated bamboo pulp used were 10 and 20% according to PP weight. The influence of acetylation and fiber content of bamboo pulp on the thermal properties of the biocomposite were investigated by using differential scanning calorimeter (DSC) and thermogravimetric analyzer (TGA). The results showed that acetylated bamboo pulp-PP biocomposite’s were higher than its pure and untreated biocomposites. The rate of crystallization growth of the acetylated bamboo pulp-PP biocomposites was faster up to 4.5 fold than pure PP composite. In addition, its acetylated bamboo pulp-PP had higher onset and maximum decomposition temperature than its untreated fiber-PP biocomposites but lower than PP. According to the results, the best thermal properties of biocomposite were obtained by acetylation of bamboo pulp with 10% fiber content.